The Role of Physical Education in Building Students’ Soft Skills: A Literature Study - Insanistyo, Bayu; Pujianto, Dian; Hussein, Ali Radhi Abdul (Journal of Pedagogy and Education Science, 2025)
Physical Education has a strategic role in developing students' physical fitness and building non-technical skills (soft skills) that are very much needed in the 21st century. The purpose of this study is to systematically examine the contribution of Physical Education in developing students' soft skills through literature studies. The research method uses the Systematic Literature Review (SLR) approach with PRISMA guidance. Data were collected from the Google Scholar and Scopus databases using the keywords "Physical Education", "Soft Skills", and "Students" for publications in 2013–2023. Of the 126 articles found, 15 met the inclusion criteria for further analysis. This literature study indicates that Physical Education plays an important role in building students' soft skills, such as leadership, teamwork, communication, self-control, and problem-solving. Various learning models such as Sport Education, Cooperative Learning, traditional games, and adaptive Physical Education have proven effective in developing these skills. However, developing soft skills through Physical Education still faces obstacles, including limited teacher competence, inadequate facilities and infrastructure, and limited learning time. In addition, there is still a research gap related to using technology-based models and longitudinal studies to see the long-term impact. Physical Education can potentially strengthen students' soft skills if it is supported by learning innovation, teacher capacity building, and a curriculum responsive to students' character development needs.